PERCEPTION OF LIVING IN LOW-INCOME HOUSING Case study: Petogogan Row Houses - Ristya Arinta Safitri (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2019)
ABSTRACTIndonesia has backlog issue against landed houses. While the needs of houses increase every year, land availability decreases in cities that causes landed house prices become unaffordable. One of the solutions offered by the government is RISHA (Rumah Instan Sederhana Sehat) or a simple design innovation of healthy house especially for low-income family. One of its successful projects was Petogogan Row Houses. However, after few years of occupancy the occupants perceive that there are some things which are considered incompatible with the rooms they inhabit. The qualitative approach applied in this study is to uncover the occupants’ perception of the post occupancy of RISHA row houses. Through this research it was found that things that are considered inappropriate by occupants are caused by (1) the furniture (non-fixed elements) capacity exceeds the RISHA room standard; (2) the physical elements (fixed-elements) of walls and ceilings set by RISHA do not provide possibilities for occupants to install non-fixed elements; (3) inadequacy of indoor natural light capacity related to the improper occupants’ considerations.Keywords: RISHA row houses, occupants’ perception, room physical elements.